2015
DOI: 10.1177/014556131509401207
|View full text |Cite
|
Sign up to set email alerts
|

Button Battery Injuries in the Pediatric Aerodigestive Tract

Abstract: Children with a button battery impaction present with nonspecific symptoms that may account for a delay in medical care. We conducted a retrospective study of the clinical presentation, management, and complications associated with button battery ingestion in thepediatric aerodigestive tract and to evaluate the associated longterm morbidity. We reviewed the medical records of 23 patients who were treated for button battery impaction at our tertiary care children's hospitalfrom Jan. 1,2000,. through July 31,201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 20 publications
2
41
2
1
Order By: Relevance
“…Wurzel et al also endorses early interval bronchoscopy to monitor tracheal mucosal healing for batteries lodged specifically in the airway [7]. However, the lack of immediate visual evidence of extensive injury at time of initial removal does not rule out more serious follow-on injury [16]. Thus, there remains a need for additional factors to consider when managing patients after initial removal.…”
Section: Discussionmentioning
confidence: 99%
“…Wurzel et al also endorses early interval bronchoscopy to monitor tracheal mucosal healing for batteries lodged specifically in the airway [7]. However, the lack of immediate visual evidence of extensive injury at time of initial removal does not rule out more serious follow-on injury [16]. Thus, there remains a need for additional factors to consider when managing patients after initial removal.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal BB impaction occurs more frequently than esophageal and can cause septal necrosis and perforation, synechia, and long-term sequelae, such as saddle nose deformity. [1][2][3][4][5][6][7][8][9][10][11][12] Lou reported that septal perforation developed in seven of nine BB cases. They speculated that in the two other cases that did not develop septal perforation, weak acidic seawater spray had been used, and this neutralized the alkaline effect of the BBs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fact that aspiration has the potential to cause a nasal foreign body to become a bronchial foreign body should be kept in mind. 1,8,9 The esophagus has room for a lodged battery for a mitigation fluid to move around it and help protect the mucosa. In the nasal cavity, where a rigid cartilaginous septum and turbinate bone are more tightly pressed around the battery, the ability to get fluids around and in between are quite limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of visual evidence of extensive injury at the time of removal does not rule out potential future injury. 13 Therefore, a repeat oesophagoscopy is recommended for disc battery impaction duration greater than 2–3 h, an impacted battery located close to the aorta, a battery with greater than 1.5 V, or concern for heavy metal or lithium toxicity. 14 A long-term sequelae of the ingested disc battery was not seen in our patient due to short duration of exposure to disc battery.…”
Section: Discussionmentioning
confidence: 99%